2016
DOI: 10.1038/mt.2016.109
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of Discoidin Domain Receptor 2 (DDR2) Prevents Myofibroblast Activation and Neovessel Formation During Pulmonary Fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a lethal human disease with short survival time and few treatment options. Herein, we demonstrated that discoidin domain receptor 2 (DDR2), a receptor tyrosine kinase that predominantly transduces signals from fibrillar collagens, plays a critical role in the induction of fibrosis and angiogenesis in the lung. In vitro cell studies showed that DDR2 can synergize the actions of both transforming growth factor (TGF)-β and fibrillar collagen to stimulate lung fibroblasts to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 63 publications
6
53
0
Order By: Relevance
“…RNA originated from cryopreserved tissues or cultured cells were extracted by TRIZol agent (Thermo Fisher Scientific, Waltham, MA, USA) and was reverse transcribed by Transcriptor First Strand cDNA Synthesis Kit (Roche, Basel, Switzerland). The expressions of mRNA and miRNA were then detected by quantitative real-time PCR (qRT-PCR) by applying the SYBR Green PCR Master Mix (Thermo Fisher Scientific, Waltham, MA, USA) as described earlier [13]. GAPDH and U6 were used as internal reference controls.…”
Section: Rna Isolation and Qrt-pcrmentioning
confidence: 99%
“…RNA originated from cryopreserved tissues or cultured cells were extracted by TRIZol agent (Thermo Fisher Scientific, Waltham, MA, USA) and was reverse transcribed by Transcriptor First Strand cDNA Synthesis Kit (Roche, Basel, Switzerland). The expressions of mRNA and miRNA were then detected by quantitative real-time PCR (qRT-PCR) by applying the SYBR Green PCR Master Mix (Thermo Fisher Scientific, Waltham, MA, USA) as described earlier [13]. GAPDH and U6 were used as internal reference controls.…”
Section: Rna Isolation and Qrt-pcrmentioning
confidence: 99%
“…LAIR‐1 signalling also reduced human neutrophil NET formation following ex vivo treatment with agonistic anti‐LAIR‐1 antibodies . Mice lacking tyrosine kinase collagen receptors discoidin domain receptors 1 and 2 (DDR1 and DDR2) are known to be protected from pulmonary fibrosis; however, these receptors also appear to regulate the function of immune cells. DDR1 signalling is important in macrophage migration and production of NO, two functions key to the ability of macrophages to respond to pathogens .…”
Section: Effects Of Fibrosis On Innate Immunitymentioning
confidence: 99%
“…The DDR family, consisting of DDR1 and DDR2, are receptor tyrosine kinases and their intracellular domains can be induced into a sustained tyrosine-phosphorylated state in response to collagen binding, which ultimately triggers an array of signalling pathways and cellular effects [ 19 , 20 ]. Recently, it was suggested that DDRs are also able to elicit influence on cells in a ligand binding-independent manner [ 21 , 22 ]. Integrins are totally different from DDRs in that they are heterodimers formed by noncovalent association of one α subunit (of which there are at least 18) and one β subunit (of which there are at least eight), and do not have the kinase activity [ 23 ].…”
Section: Introductionmentioning
confidence: 99%